(untitled) (SCIÉNDO INGENIUM, 2022)
This research deals with a generalized problem in our country where, given the increase in aggressions against women or members of the family group, the State intends to reduce or avoid them by resorting to the use of Criminal Law, sanctioning said conduct with effective custodial penalties. Our main objective was to demonstrate what was the legal effect of the intervention of Criminal Law in minor crimes due to Family Violence in the District of Santa during the years 2018 and 2019, using correlational, legal hermeneutical methods and as techniques the interview, the documentary analysis, case studies and descriptive statistics. Concluding that about 80% of cases, after requiring the investment of a large amount of human and economic resources, ended up being archived because the party aggrieved by the scarce harmfulness of the facts no longer attends the Fiscal Office to provide more information or to be evaluated medically, legally or psychologically, evidencing a tacit conciliation between the parties, which means that the criminalization of this type of conduct has not contributed to reducing its incidence and rather the State Policy for the protection of the family.